Needs Analysis of Integrated Ethno-Socioscientific Multimedia to Enhance Elementary Students’ Environmental Awareness - Helga Salsabila; Agus Mukti Wibowo; Samsul Susilawati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This research is driven by the